2014
DOI: 10.1002/pbc.24940
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology reports for childhood brain tumor survivors: Implementation of recommendations at home and school

Abstract: Patient understanding and willingness play a significant role in the implementation of neuropsychology recommendations. Collaboration and clear communication between the patient, teacher, parent, and neuropsychologist is vital for effective management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 23 publications
3
61
0
Order By: Relevance
“…Routine clinical management should be central to the rehabilitation of children with pCMS, with a systematic integrated approach to the management, assessment and treatment of speech and language disorders, and followup and early intervention. It is therefore recommended that rehabilitation of speech and language in children with pCMS involves multi-phase implementation of evidencebased guidelines and recommendations that identify and highlight risk factors, specific deficits, and knowledge about progression over time [9,13,38]. In summary, it is recommended that integrated, holistic rehabilitation of pCMS involves the following stages:…”
Section: Rehabilitation Of Speech and Language Problems During And Afmentioning
confidence: 99%
“…Routine clinical management should be central to the rehabilitation of children with pCMS, with a systematic integrated approach to the management, assessment and treatment of speech and language disorders, and followup and early intervention. It is therefore recommended that rehabilitation of speech and language in children with pCMS involves multi-phase implementation of evidencebased guidelines and recommendations that identify and highlight risk factors, specific deficits, and knowledge about progression over time [9,13,38]. In summary, it is recommended that integrated, holistic rehabilitation of pCMS involves the following stages:…”
Section: Rehabilitation Of Speech and Language Problems During And Afmentioning
confidence: 99%
“…The sum of report quality ratings was higher for the new (shortened, more readable, and restructured for clarity) report format -Bodin, 2007 82% of parents endorsed general satisfaction with services Factor analysis of items indicated four factors: 1) general satisfaction, 2) acceptance/empathy, 3) provision of help, and 4) facilities/ administrative assistance Satisfaction ratings were highest for general satisfaction, acceptance/empathy, and facilities/ administrative assistance Provision of help ratings were lower than other satisfaction factors, and a large minority of participants (45%) did not endorse that the evaluation improved their child's life Parents for whom maternal education was some college or a college degree were less satisfied than parents for maternal education was either lower or higher Cheung, 2014 All parents and teachers were "satisfied with the support they received from the neuropsychologist" Report quality was generally described positively, though a few (4 out 15) parents found some aspects of the report confusing When asked for suggestions to improve services, parents requested, 1) more follow-up with the neuropsychologist ( Nowinski, 2009 Overall satisfaction was high, and decreased marginally from the post-feedback to postevaluation time points Alliance increased between testing and feedback time points on the Collaboration, Agreement on Goals, and Bond subscales Ratings of satisfaction were generally high, both post-feedback and five months later. However, satisfaction did decrease over that time frame Lowest rated item was parent report of being "less stressed" after evaluation -…”
Section: Parent Satisfaction With Service Componentsmentioning
confidence: 98%
“…Regarding broad parent satisfaction, all studies indicated that the majority of parents had a positive experience with the neuropsychological services their children received. In many studies, high ratings were nearly unanimous, such that 94-100% of parents reported satisfaction with neuropsychological services (Cheung et al, 2014;Dodd et al, 2018;Farmer & Brazeal, 1998;Kirkwood et al, 2017;Nissirios et al, 2018;Stark et al, 2014). However, in two of the largest studies, ratings of broad satisfaction indicated that 10-20% of parents were not satisfied with the services (Bodin et al, 2007;Waber et al, 2017).…”
Section: Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is paucity in literature on parent and child satisfaction of these assessments, 5,6,7 and no identified literature on whether recommendations are implemented. 8,9 This study aimed to assess levels of satisfaction amongst parents and children with TS following neuropsychological assessment, and investigate the proportion of recommendations implemented at home and school. Method All children who underwent a neuropsychological assessment in a specialist TS clinic from 2013 -2016 were identified.…”
mentioning
confidence: 99%